(untitled) - Landau, Rubin H.. (Weinheim, 2015)
This upper-division text provides an unusually broad survey of the topics of modern computational physics from a multidisciplinary, computational science point of view. Its philosophy is rooted in learning by doing (assisted by many model programs), with new scientific materials as well as with the Python programming language. Python has become very popular, particularly for physics education and large scientific projects. It is probably the easiest programming language to learn for beginners, yet is also used for mainstream scientific computing, and has packages for excellent graphics and even symbolic manipulations.
Vật lý tính toán nâng cao
Keywords: Physics,Mathematical physics,Vật lý,Toán học vật lý,Physics,Vật lý; Computer simulation,Mô phỏng máy tính